2000
DOI: 10.1590/s0104-11692000000600008
|View full text |Cite
|
Sign up to set email alerts
|

Não vou esquecer nunca!: a experiência feminina com o abortamento induzido

Abstract: PEDROSA, I.L.; GARCIA, T.R. "Não vou esquecer nunca!": a experiência feminina com o abortamento induzido.Rev.latino-am.enfermagem, Ribeirão Preto, v. 8, n. 6, p. 50-58, dezembro 2000. INTRODUÇÃOO abortamento induzido voluntariamente pela mulher é considerado uma importante questão de saúde pública, por estar intimamente associado ao problema da mortalidade materna. Sem dúvida alguma, é um fenômeno social dos mais complexos e multifacetados, sua menção fazendo emergir opiniões divergentes, seja no campo ético,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
0
9
0
6
Order By: Relevance
“…De forma convergente, registram relatos ambíguos das mulheres, conjugando sentimentos de mal-estar físico ou emocional com alívio e bem-estar 44,45 .…”
Section: Aborto E Saúde Mentalunclassified
“…De forma convergente, registram relatos ambíguos das mulheres, conjugando sentimentos de mal-estar físico ou emocional com alívio e bem-estar 44,45 .…”
Section: Aborto E Saúde Mentalunclassified
“…O abortamento provocado traz consigo um estigma, vinculado à crime, à pecado. Estes preconceitos e tabus acarretam sérios problemas psicossociais, levando muitas mulheres a enfrentarem sozinhas A mulher em situação de abortamento: um enfoque existencial 6 5 a internação a fim de não serem identificadas pela sociedade, nem serem alvos de curiosidade (28) .…”
Section: Como Uma Experiência Que Requer Uma Hospitalização Que Se Mounclassified
“…Research 5 conducted has verified that women that induced abortion showed feelings of anxiety and fear from the confirmation of the pregnancy up to the time of the decision, as well as insecurity in relation to the reaction of partners with regard to the pregnancy. Considering the diversity of the feelings provoked and personal and social influences, the risks of post-abortion psychological disturbances has increased, with emotional and social support fundamental.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Family support, especially from partners, helps psychological adjustment, and when absent is associated with depression and anxiety. 8 Fragile and unstable relationships and women's concern about men's reactions are indicated in the literature, 9,5 with abortion often based on insecurity in the relationship and feelings of abandonment and neglect by the partner. Financial difference associated with lack of support by the father of the baby and unstable martial relationship are justifications associated with the practice of abortion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation